Digital Archives Management: Improving Operational Efficiency and Information Security: Manajemen Arsip Digital: Meningkatkan Efisiensi Operasional dan Keamanan Informasi - Ari Nur Aliyah Rohalia; Ilmi Usrotin Choiriyah; Desy Triana Afdillah; Khalimatus Sa'diyah; Rizki Yefin Saputri; Muhammad Prayoga Arianto (International Consortium of Education and Culture Research Studies, 2025)
General Background Efficient records management constitutes a fundamental administrative requirement for maintaining institutional memory, ensuring accountability, and supporting strategic decision-making. Specific Background Educational institutions in Indonesia are currently navigating the transition from traditional paper-based document storage to modern electronic environments to accommodate growing administrative demands. Knowledge Gap Although theoretical frameworks advocate for fully integrated automated archiving platforms, practical implementation within public schools frequently encounters severe operational bottlenecks regarding specialized human resources and technical infrastructure. Aims This qualitative case study evaluates the records administration workflow within a public secondary school to identify prevailing operational limitations. Results The analysis reveals that the institution utilizes systematic manual procedures encompassing document creation, physical storage, and environmental maintenance; however, the transition to electronic platforms faces substantial barriers, including inadequate specialized personnel, limited physical infrastructure, restricted retrieval speed, and compromised information security. Novelty This research distinctly isolates the specific administrative vulnerabilities that emerge when high-volume educational facilities attempt electronic document transitions without adequate specialized technical personnel. Implications Sustaining long-term institutional accountability requires educational stakeholders to prioritize the digitization of physical documents, implement integrated electronic tracking systems, and consistently train staff in contemporary data security protocols. Highlights: Limited technical infrastructure and personnel shortages severely restrict document retrieval speed and data confidentiality. Systematic manual procedures remain the primary method for document preservation and environmental maintenance. Integrating electronic tracking platforms requires continuous staff training and targeted facility investments. Keywords: Information Security, Records Retrieval, Public Education, Data Storage, Organizational Accountability